THE AMERICANIZATION OF SUPER SENTAI IN THE POWER RANGERS TELEVISION SERIES - Pasopati, Rommel Utungga; Hamdani, Farham Nazhib; Putra, Ananda Syahromi; Andharu, Devito; Fadillah, Muhammad Reza Ishadi (PARADIGM: Journal of Language and Literary Studies, 2024)
This article investigates matters of Americanization in the adaptation of Power Rangers superhero serials to be imbued with American values from its original Japanese version entitled Super Sentai. Even though transcultural serials are considered successful in the United States and worldwide, they are deemed culturally problematic. Through a qualitative method and an explorative approach, the analysis explores that Power Rangers’ adaptation is shadowed by gender, racial, and second character issues. For instance, the gender aspect is related to gender swap, pink rangers, and the wearing of skirts by female rangers. Racial issues cover matters of the idealized melting pot in the U.S. Second character issues include matters of child employment, demonized monsters, and the usage of armed weapons. In conclusion, while Power Rangers is commercially successful, its adaptation process selectively modifies cultural elements, presenting an idealized rather than an authentic reality.